2015
DOI: 10.2217/fvl.15.18
|View full text |Cite
|
Sign up to set email alerts
|

HSV-I and the Cellular DNA Damage Response

Abstract: Peter Wildy first observed genetic recombination between strains of HSV in 1955. At the time, knowledge of DNA repair mechanisms was limited, and it has only been in the last decade that particular DNA damage response (DDR) pathways have been examined in the context of viral infections. One of the first reports addressing the interaction between a cellular DDR protein and HSV-1 was the observation by Lees-Miller et al. that DNA-dependent protein kinase catalytic subunit levels were depleted in an ICP0-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 112 publications
0
58
0
Order By: Relevance
“…As for the effects of HSV1 infection on damage and repair of host cell DNA, studies have more often been concerned with the reverse—the use of the cell's DNA damage response (DDR) for repairing the viral DNA (92). Among those who have examined viral‐induced damage in the host DNA, Aranda‐Anzaldo (93) showed that HSV1 infection of cultured cells induced SSBs in the host cell DNA in a time‐dependent fashion and that the early DNA damage observed in virus‐infected cells was related to modifications in the higher‐order structure of host‐cell chromatin (94).…”
Section: Dna Damage and Repair In Ad And Hsv1mentioning
confidence: 99%
“…As for the effects of HSV1 infection on damage and repair of host cell DNA, studies have more often been concerned with the reverse—the use of the cell's DNA damage response (DDR) for repairing the viral DNA (92). Among those who have examined viral‐induced damage in the host DNA, Aranda‐Anzaldo (93) showed that HSV1 infection of cultured cells induced SSBs in the host cell DNA in a time‐dependent fashion and that the early DNA damage observed in virus‐infected cells was related to modifications in the higher‐order structure of host‐cell chromatin (94).…”
Section: Dna Damage and Repair In Ad And Hsv1mentioning
confidence: 99%
“…HSV-1 has significant connections with all three DDR pathways (17). ICP0 is recognized to block DNA-PK function by targeting its catalytic subunit for proteasomal degradation (2,18,19).…”
mentioning
confidence: 99%
“…Viruses have developed unique strategies to circumvent host cell responses, while others hijack cellular DNA damage response proteins for their propagation or replication. Similar to BoHV-1, homologous recombination repair is also inhibited during HSV-1 infection (41). Furthermore, murine gamma herpesvirus 68 (␥HV68) M2 protein interacts with the DNA repair complex, DDB1/ATM/COP9/cullin (14).…”
Section: Discussionmentioning
confidence: 99%